Analisis Dan Perancangan Sistem Informasi Layanan Pajak Daerah Pada Badan Pengelola Pajak Dan Retribusi Daerah Kota Jambi - Purnomo, M. Arief; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
The Jambi City Regional Tax and Retribution Management Agency has the main task of assisting the Regional Head in carrying out the affairs of the Regional Government in the field of income and other assistance tasks by planning, developing and controlling the sources of regional tax revenues which include; Revenue, Determination, Billing, Planning and Reporting, Control and Extension of Administration / Secretariat and carry out other tasks given by the Regional Head in accordance with their fields. Jambi City Regional Tax and Retribution Management Agency in managing local taxes, for now the restaurant taxpayer reporting process is still reporting taxes manually. Where: 1) Taxpayers must go to the Jambi City BPPRD office to report the tax. 2) The waiting time for taxpayers in Jambi City BPPRD office and the accumulation of taxpayers if it is near the due date. 3) The length of the verification, calculation and determination process by the officer. 4) Taxpayers must wait again for the tax payment process at the Bank. To solve these problems the researchers designed the Regional Tax Service Information system with the aim of becoming an alternative problem solving. In the design and analysis researchers use the UML method and design designs using prototypes. From the results of the analysis and design produces useful features for taxpayers such as 1) The system also stores employee / staff data. 2) The system also stores taxpayer data (hotels and restaurants). 3) Taxpayers can see information when the tax reporting due date. 4) Taxpayers can report from their home or place of business without having to come to the office of the Jambi City Regional Tax and Retribution Agency.